A comparison of two strategies to assess sexual violence: general vs. specialised trauma screening strategies in two high-risk substance use health disparity samples - RaeAnn E. Anderson; Anne E. Nickell; Danielle M. Piggott; Alec P. Boros; Douglas L. Delahanty (European Journal of Psychotraumatology, 2023)
ABSTRACTBackground/Objective: Using two different high-risk samples, the present study compared and contrasted two different strategies/questionnaire types for assessing a history of sexual violence: a general trauma screening vs. specialised behaviourally-specific questionnaires.Methods: Sample 1 included 91 men and women seeking detoxification treatment services in a publicly funded, urban clinic who completed a trauma and substance use questionnaire battery during treatment. Sample 2 included 310 women at a rural college who completed a trauma and religious coping questionnaire battery for course credit. All participants completed both types of questionnaires: One general trauma screening questionnaire (i.e. the Life Events Checklist [LEC]) and two behaviourally-specific specialised questionnaires (i.e. the 2007 Sexual Experiences Survey [SES] and the Childhood Trauma Questionnaire [CTQ]).Results: There were large differences in the cases identified by the behaviourally-specific questionnaires (SES and CTQ) compared to the general trauma screening questionnaire (the LEC) in both samples but few differences in the prevalence rates of sexual violence detected by each questionnaire type. In the detoxification sample, the differences were especially notable for men. Follow-up analyses indicated that degree of traumatisation impacted results likely by increasing participant’s willingness to endorse face-valid items on the LEC.Conclusions: For men, the behaviourally-specific questionnaires (SES/CTQ) were necessary to identify cases. For those with more severe trauma histories, the LEC was equivalent to the SES/CTQ in identifying a similar number of sexual violence cases. Thus, clinicians and researchers should consider the population when selecting assessments to identify sexual violence history.